Mutual Shaping of Circadian Body-Wide Synchronization by the Suprachiasmatic Nucleus and Circulating Steroids - Yao, Yifan; Silver, Rae (Frontiers in Behavioral Neuroscience, 2022)
Background Steroids are lipid hormones that reach bodily tissues through the systemic circulation, and play a major role in reproduction, metabolism, and homeostasis. All of these functions and steroids themselves are under the regulation of the circadian timing system (CTS) and its cellular/molecular underpinnings. In health, cells throughout the body coordinate their daily activities to optimize responses to signals from the CTS and steroids. Misalignment of responses to these signals produces dysfunction and underlies many pathologies. Questions Addressed To explore relationships between the CTS and circulating steroids, we examine the brain clock located in the suprachiasmatic nucleus (SCN), the daily fluctuations in plasma steroids, the mechanisms producing regularly recurring fluctuations, and the actions of steroids on their receptors within the SCN. The goal is to understand the relationship between temporal control of steroid secretion and how rhythmic changes in steroids impact the SCN, which in turn modulate behavior and physiology. Evidence Surveyed The CTS is a multi-level organization producing recurrent feedback loops that operate on several time scales. We review the evidence showing that the CTS modulates the timing of secretions from the level of the hypothalamus to the steroidogenic gonadal and adrenal glands, and at specific sites within steroidogenic pathways. The SCN determines the timing of steroid hormones that then act on their cognate receptors within the brain clock. In addition, some compartments of the body-wide CTS are impacted by signals derived from food, stress, exercise etc. These in turn act on steroidogenesis to either align or misalign CTS oscillators. Finally this review provides a comprehensive exploration of the broad contribution of steroid receptors in the SCN and how these receptors in turn impact peripheral responses. Conclusion The hypothesis emerging from the recognition of steroid receptors in the SCN is that mutual shaping of responses occurs between the brain clock and fluctuating plasma steroid levels.